Environmental Issues & Implications of Cryptocurrency Market: A Theoretical Study - P. , Mary Jeyanthi; S. , Radha Rammohan (International Journal of Psychosocial Rehabilitation, 2020)
This paper decides to discuss the environmental issues & implications of the cryptocurrency market. Since many studies and research have already happened regarding cryptocurrencies and blockchain working methodologies, only a couple of papers discussed the environmental perspectives and their impact on the growth of these digital asset modules. It is very hard to believe that the world was without the Internet, air conditioners, vehicles, or cash. Technology plays a major role in every individual’s life and environment. Now the serious implications are environmental issues. People are living longer with technology, and anyway, it does come with a price. Cryptocurrency, or virtual currency, is the money of the future. In this digital age, cryptocurrencies have become a global phenomenon. Even though bankers, scientists, and developers have limited knowledge about cryptocurrencies. Despite its virtual nature, Bitcoin mining requires a massive amount of processing power and, in line, energy. One of the major problems is still not being effectively addressed, namely, the energy consumption of transacting across many of the biggest blockchain networks in the industry. This issue, which has grown exponentially over the past few years, shows no signs of slowing down and continues to cause environmental degradation along the way. Since this paper provides the current insights into the environmental issues and discusses the possible alternatives, we need to adhere to them in the future.